Comparison of varsity female basketball student-athletes’ preferences for coach’s leadership behaviours and coach’s gender between Malaysia and Iran / Bita Sobhanzadeh and Lim BH - Sobhanzadeh, Bita; Lim, BH (Faculty of Sport Science and Recreation, Universiti Teknologi MARA, 2013)
The main purpose of this study was to examine and compare the varsity female basketball student-athletes’ preferences for coach’s leadership behaviours and coach’s gender between Malaysia and Iran. A demographic form and the Revised Leadership Scale for Sport (RLSS) were employed in the current study. Descriptive statistics indicated that subjects preferred that their coaches have high DB, while the AB was the lowest value. Results of MANOVA indicated that there were significant differences [F (6, 105) = 12.614, P < 0.05; Wilks’ Lambda = 0.581] for coach’s leadership behaviours between Malaysia and Iran. Iranian varsity female basketball student-athletes had significantly higher preference scores in Positive Feedback [F (1, 110) =17.59, P < 0.05], Training & Instruction [F (1, 110) =13.37, P < 0.05], and Social Support [F (1,110) = 17.28, P < 0.05] than Malaysian athletes, while Malaysian varsity female basketball student-athletes had significant differences higher for Situational Consideration [F (1, 110) =7.89, P < 0.05]. Chi-Square statistic was computed that there were significant differences [x2 (1, 112) = 14.29, P < 0.05] in a preferences for male coaches. Since, these findings exhibited that varsity female basketball student-athletes between both countries preferred different leadership behaviours and had a preference for male coaches; it suggests that coaches be aware of their athletes’ preferences of leadership behaviour and also using various leadership methods according to the female athletes’ needs and cultural differences that may force significant changes to their normal coaching.